Knowledge, attitude and practice of self-wound management among patients with diabetic foot ulcer (DFU) in Pahang - Saidi, Sanisah; Farouzy, Hamizah (IIUM Press, 2017)
A survey in 2011 reported that the prevalence of diabetes in Malaysia is 20.8% (2.8 million people) and 88% have uncontrolleddiabetes. Diabetic foot ulcer (DFU) is one of the common diabetes complications in Malaysia that leads to other devastated situation including infection, amputation and death. In Pahang, 95% of the patients have uncontrolled diabetes and 50% of them suffered from DFU. Self-wound management is an important element in reducing the risk of further complications of DFU. However, little is known on the patients' understanding of diabetes and their practice of selfwound management. This study aimed to understand the knowledge, attitude and practice of self-wound management among patients with diabetic ulcer in Pahang.